Hereditary and acquired complement dysregulation in membranoproliferative glomerulonephritis - Licht, Christoph; Fremeaux-Bacchi, Veronique (Thrombosis and Haemostasis, 2009)
Membranoproliferative glomerulonephritis (MPGN) is a chronic progressive renal disease that is diagnosed on the basis of renal histological features. Several MPGN subtypes have been defined by the localization and composition of glomerular deposits (electron dense, Ig and C3). MPGN II or dense deposit disease (DDD) which is defined by the occurrence of electron dense deposits within the lamina densa of the glomerular basement membrane (GBM) is strongly associated with dysregulation of the alternative complement pathway (AP). However, C3 Nephritic Factor (C3NeF), an autoantibody against the alternative C3 convertase C3bBb, and mutations in regulatory proteins of the AP have also been identified in other subtypes of MPGN and even in glomerulonephritis with mesangial C3 deposits. Clinically, MPGN is characterized by proteinuria (up to nephrotic range) and hypertension, frequent progression to end-stage kidney disease and disease recurrence after renal transplantation. The age of onset varies from childhood to adulthood. In the following we will review our current knowledge of pathogenesis of MPGN and will present a novel classification system of the disease based on pathogenesis rather than on morphology. A better understanding of the pathogenesis of MPGN is crucial for the development of novel, specific treatment strategies.
Keywords: Membranoproliferative glomerulonephritis; haemolytic uremic syndrome; complement system; C3 deposition; glomerulonephritis C3 (GNC3); C3 deposition glomerulopathy (C3DG); Factor H (CFH)